2014
DOI: 10.1371/journal.pone.0090674
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Efficacy of Contrast-Enhanced Ultrasound, Acoustic Radiation Force Impulse Imaging, and Their Combined Use in Differentiating Focal Solid Thyroid Nodules

Abstract: BackgroundA key limitation of conventional ultrasound (US) includes poor differentiation of benign from malignant thyroid nodules. Contrast-enhanced US (CEUS) and acoustic radiation force impulse (ARFI) could provide better characterization of focal thyroid nodules; however, no studies have compared their efficacies.ObjectiveTo evaluate the diagnostic efficacy of conventional US,CEUS, ARFI, and their combined use in differentiating focal solid thyroid nodules.MethodsOne-hundred-forty-six Chinese patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 19 publications
4
70
1
1
Order By: Relevance
“…CEUS involves the use of a contrast medium that enhances the diagnostic imaging capabilities of traditional medical sonography and is a milestone for diagnostics in liver tumors, with recent studies evaluating similar application of CEUS in characterizing thyroid gland tumors (18)(19)(20)(21)(22)(23). In addition, CEUS performed with the use of a microbubble contrast agent may be a potentially useful adjunct in assessing thyroid nodules, since it has a high specificity of 84.8% and high sensitivity of 76.9% (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CEUS involves the use of a contrast medium that enhances the diagnostic imaging capabilities of traditional medical sonography and is a milestone for diagnostics in liver tumors, with recent studies evaluating similar application of CEUS in characterizing thyroid gland tumors (18)(19)(20)(21)(22)(23). In addition, CEUS performed with the use of a microbubble contrast agent may be a potentially useful adjunct in assessing thyroid nodules, since it has a high specificity of 84.8% and high sensitivity of 76.9% (21).…”
Section: Introductionmentioning
confidence: 99%
“…CEUS is also amenable to combination approaches, and dynamical evaluation of microcirculation with CEUS in combination with color-coded and power Doppler sonography was demonstrated to yield reliable preoperative results in the Contrast-enhanced ultrasound and real-time elastography in the differential diagnosis of malignant and benign thyroid nodules characterization of thyroid adenomas (22). Furthermore, the combination of CEUS with acoustic radiation force impulse (ARFI) has been shown to significantly improve the diagnostic accuracy of thyroid nodules (23). As a noninvasive technique for evaluating thyroid nodules, US-based elastography encompasses a variety of approaches, including RTE, acoustic radiation force impulse imaging and supersonic shear imaging (24).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Yuan et al a higher value of this sign was observed, as shown by 78% sensitivity and 95% specificity (Yuan et al, 2015). Deng et al also used this feature with similar sensitivity and specificity: 82% and 85%, respectively (Deng et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…The results are ambiguous and sometimes contradictory. The diagnostic value of CEUS has been analysed in only very few studies (Ferrari et al, 2008;Zhang et al, 2010;Nemec et al, 2012;Cantisani et al, 2013;Giusti et al, 2013;Deng et al, 2014;Ma et al, 2014), yielding variable results; the sensitivity varies between 68-100% and specificity -between 67-594%.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors reported that hypoenhancement is the most accurate US feature of malignancy on CEUS with high sensitivity, specificity and accuracy 82%, 85%, and 84%, respectively [23][24][25][26][27]. Three recent meta-analyses reported high-pooled accuracy of CEUS in diagnosing benign from malignant nodules with sensitivity, specificity, and positive and negative LR ranging 0.85-0.88, 0.87-0.90, 5.8-8.6 and 0.15-19 respectively [27][28][29].…”
Section: Conventional B-mode Ultrasoundmentioning
confidence: 99%